2023
DOI: 10.3390/foods12071414
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Preharvest Melatonin on Soft Rot and Quality of Kiwifruit Based on Principal Component Analysis

Abstract: Botryosphaeria dothidea is the source of the deadly kiwifruit disease known as soft rot. In order to explore the role of melatonin in regulating the postharvest quality and disease resistance of kiwifruit at different growth and development stages, in this study, we applied melatonin at different concentrations to kiwifruit at the young fruit, expansion, and late expansion stages to assess its effect on fruit resistance to B. dothidea, minimize soft rot, and maintain postharvest fruit quality. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
(61 reference statements)
0
6
0
Order By: Relevance
“…Therefore, asparagus varieties with a low dry matter content, like Jingzilu 2, and Guelpin Millennium, will taste more hydrated. Asparagus varieties rich in saponins and selenium may have more antitumor effects (Kim et al., 2021 ; Peng et al., 2023 ), such as Atlas and Appolo, Walker noble, and Jinglvlu 3, which are the top two varieties in protodioscin and the mineral selenium, respectively. Jinggang 111, Appolo, Jingke 3, and Jingke 2 may have relatively stronger antioxidant and whitening effects, as their total phenols and flavonoid contents are higher (Ferreyra et al., 2012 ; Smeriglio et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, asparagus varieties with a low dry matter content, like Jingzilu 2, and Guelpin Millennium, will taste more hydrated. Asparagus varieties rich in saponins and selenium may have more antitumor effects (Kim et al., 2021 ; Peng et al., 2023 ), such as Atlas and Appolo, Walker noble, and Jinglvlu 3, which are the top two varieties in protodioscin and the mineral selenium, respectively. Jinggang 111, Appolo, Jingke 3, and Jingke 2 may have relatively stronger antioxidant and whitening effects, as their total phenols and flavonoid contents are higher (Ferreyra et al., 2012 ; Smeriglio et al., 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The PCA method has been widely used to evaluate the quality of agricultural products such as kiwifruit, jujubes, foxtail millet, and jasmine tea (An et al., 2023 ; Peng et al., 2023 ; Singh et al., 2023 ; Zhao et al., 2023 ). By reducing the dimensionality of the data and eliminating overlapping information from numerous sources, the evaluation process was simplified, making it faster and more accurate than a single evaluation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al [50] utilized PCA and correlation analysis to reveal that short-term temperature treatments changed the metabolic flow, with GABA indicating positive correlations with sugars and organic acids. Peng et al [51] conducted a comprehensive evaluation of 15 quality indices using PCA, determining that a 300 µmol/L MT treatment significantly enhanced disease resistance and preserved kiwifruit quality. The PCA results in this study demonstrated that the first three principal components collectively contributed to 78.789% of the variance.…”
Section: Discussionmentioning
confidence: 99%
“…Soluble protein content was determined by the G-250 method 24 by adding a small amount of distilled water and grinding to homogenate, centrifuging at 5000 r/min for 10 min, taking the supernatant and adding the G-250 reagent to mix it thoroughly, and then leaving it to stand at room temperature for 2 min before colourimetry was carried out at 595 nm.…”
Section: Methodsmentioning
confidence: 99%